Answer:
1) 512
2) 27
3) 216
4) 8
5) 343
6) 729
Explanation:
1)(8^4)^3/4 = 8^3 [using the power of power rule]
=8*8*8
= 512
2) The second can be written as (81)^3/4
81 = 3^4
Therefore, (3^4)^3/4 = 3^3
= 27
3) 1296 = 6^4
Therefore, (1296)^3/4 = (6^4)^3/4
= 6^3
= 216
4) 16^3/4 = (2^4)^3/4
= 2^3
= 8
5) 2401 = 7^4
The expression can be written as (2401)^3/4
= (7^4)^3/4
= 7^3
= 343
6) 6561 = 9^4
The given expression can be written as (6561)^3/4
= (9^4)^3/4
= 9^3
= 729
Hope you will understand the concept.
Thank you.